2007
DOI: 10.1002/jmv.20870
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐by‐dose virological and hematological responses to intravenous immunoglobulin in an immunocompromised patient with persistent parvovirus B19 infection

Abstract: A 42-year-old male with stage IV mantle cell lymphoma received chemotherapy and autologous peripheral blood stem cell transplantation. He developed pancytopaenia, and bone marrow examination indicated a parvovirus B19 (PVB 19)-induced red cell aplasia, confirmed by virological tests. Multiple doses of intravenous immunoglobulin (IVIG) were given over the following months, with blood samples being taken after each dose for quantitative PVB 19 DNA and hematological testing to assess the response. Each dose of IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Similar observations have been reported previously [Lefrère et al, 2005;Liefeldt et al, 2005;Dobec et al, 2007;Tang et al, 2007;Wą sak-Szulkowska et al, 2008] and the probable causes of such infections have been reviewed by . In the case of kidney graft recipient infected with genotype 2 B19V it seems that lack of viral clearance was mainly connected with immunosuppressive therapy impairing the humoral immune response.…”
Section: Discussionsupporting
confidence: 83%
“…Similar observations have been reported previously [Lefrère et al, 2005;Liefeldt et al, 2005;Dobec et al, 2007;Tang et al, 2007;Wą sak-Szulkowska et al, 2008] and the probable causes of such infections have been reviewed by . In the case of kidney graft recipient infected with genotype 2 B19V it seems that lack of viral clearance was mainly connected with immunosuppressive therapy impairing the humoral immune response.…”
Section: Discussionsupporting
confidence: 83%
“…One should be aware that acute viral myocarditis or even a sustained anaemic period after primary B19 infection could trigger the clinical manifestation of a latent chemotherapy induced cardiomyopathy. Paediatric cancer patients with severe symptoms attributable to B19 infection should be treated with standard immunoglobulins106 107; with real time quantitative PCR based techniques the response of the B19 viraemia can be quantified dose by dose 108…”
Section: Parvovirus B19mentioning
confidence: 99%
“…16 There are no randomised control trials regarding use of HNIG for treatment of parvovirus infection and most of the evidence for its efficacy is derived from case reports, with some cases demonstrating dose dependent virological and haematological response to treatment. 17 In a systematic review for the treatment regimen (immunoglobulin therapy with or without reduction of immunosuppression) of parvovirus infection in renal transplant recipients, Liefeldt et al reported that although clinical response was noted in majority of reports, virological response was either not found or not determined in a large number of studies. 18 The present case illustrates unusual presentations of infections with common pathogens can occur in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 97%